Pro website development and operations streamlining devOps for large-scale websites - Sacks, Matthew (Apress, 2012)
Pro Website Development and Operations gives you the experience you need to create and operate a large-scale production website. Large-scale websites have their own unique set of problems regarding their designproblems that can get worse when agile methodologies are adopted for rapid results. Managing large-scale websites, deploying applications, and ensuring they are performing well often requires a full scale team involving the development and operations sides of the companytwo departments that don't always see eye to eye. When departments struggle with each other, it adds unnecessary complexity to the work, and that result shows in the customer experience. Pro Website Development and Operations shows you how to streamline the work of web development and operations - incorporating the latest insights and methodologies of DevOps - so that your large-scale website is up and running quickly, with little friction and extreme efficiency between divisions. This book provides critical knowledge for any developer engaged in delivering the business and software engineering goals required to create and operate a large-scale production website. It addresses how developers can collaborate effectively with business and engineering teams to ensure applications are smoothly transitioned from product inception to implementation, and are properly deployed and managed.  Pro Website Development and Operations provides unique insights into how systems, code, and process can all work together to make large-scale website development and operations ultra-efficient.